2021
DOI: 10.33369/juridikdas.3.2.136-143
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model RME Berbasis Etnomatematika Terhadap Kemampuan Literasi Matematika Siswa Kelas IV SD Gugus 17 Kota Bengkulu

Abstract: This study aims to determine the effect of ethnomatemics based Realistic Mathematics Education models on the mathematical literacy ability of grade IV elementary school students in the 17th city of Bengkulu on flat construction material. This research is a quantitative research. The research method used was quasi-experimental research using the matching only pretest-posttest control group design. The population in this study was the Elementary School Cluster 17 Bengkulu City. The sampling technique uses cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Pembelajaran berbasis RME juga berpengaruh terhadap kemampuan literasi siswa (Witha et al, 2021;Mananggel, 2022). Hasil penelitian (Istiana et al, 2020) menemukan bahwa Pembelajaran berbasis RME dapat meningkatkan kemampuan literasi matematis siswa (Istiana et al, 2020).…”
Section: Gambar 1 Skema Hubungan Antara Komponen-komponen Yangunclassified
“…Pembelajaran berbasis RME juga berpengaruh terhadap kemampuan literasi siswa (Witha et al, 2021;Mananggel, 2022). Hasil penelitian (Istiana et al, 2020) menemukan bahwa Pembelajaran berbasis RME dapat meningkatkan kemampuan literasi matematis siswa (Istiana et al, 2020).…”
Section: Gambar 1 Skema Hubungan Antara Komponen-komponen Yangunclassified
“…Low achievement in learning mathematics is caused by the absence of cultural objects in mathematics classes (Ilono C & J.I, 2013;Mirnawati et al, 2020). The low learning outcomes in mathematics are because mathematics in classrooms is often separated from the culture of students, which should be an important object in learning mathematics (Adam, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Culture-based mathematics learning will help students demonstrate consistent mathematical processes when students reason, solve problems, communicate ideas, and choose appropriate representations through the development of everyday math practices. Several studies have shown that integrating culture into learning will improve the ability to think creatively in mathematics (Sariningisih & Kadarisma, 2016), develop critical thinking skills (Martyanti & Suhartini, 2018;Mirnawati et al, 2020), and can increase students ' mathematical understanding (Sarwoedi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%